Elevated lipoxygenase and cytochrome P450 products predict progression of chronic kidney disease. Issue 2 (25th July 2018) - Afshinnia, Farsad; Zeng, Lixia; Byun, Jaeman; Wernisch, Stefanie; Deo, Rajat; Chen, Jing; Hamm, Lee; Miller, Edgar R; Rhee, Eugene P; Fischer, Michael J; Sharma, Kumar; Feldman, Harold I; et al.
Abstract: Background: The clinical relevance of arachidonic acid (AA) metabolites in chronic kidney disease (CKD) progression is poorly understood. We aimed to compare the concentrations of 85 enzymatic pathway products of AA metabolism in patients with CKD who progressed to end-stage kidney disease (ESKD) versus patients who did not in a subcohort of Chronic Renal Insufficiency Cohort (CRIC) and to estimate the risk of CKD progression and major cardiovascular events by levels of AA metabolites and their link to enzymatic metabolic pathways. Methods: A total 123 patients in the CRIC study who progressed to ESKD were frequency matched with 177 nonprogressors and serum eicosanoids were quantified by mass spectrometry. We applied serum collected at patients' Year 1 visit and outcome of progression to ESKD was ascertained over the next 10 years. We used logistic regression models for risk estimation. Results: Baseline 15-hydroxyeicosatetraenoate (HETE) and 20-HETE levels were significantly elevated in progressors (false discovery rate Q  ≤ 0.026). The median 20-HETE level was 7.6 pmol/mL [interquartile range (IQR) 4.2–14.5] in progressors and 5.4 pmol/mL (IQR 2.8–9.4) in nonprogressors (P < 0.001). In an adjusted model, only 20-HETE independently predicted CKD progression. Each 1 standard deviation increase in 20-HETE was independently associated with 1.45-fold higher odds of progression (95% confidence interval 1.07–1.95; P = 0.017). Principal components of lipoxygenase (LOX) and cytochrome P450 (CYP450) pathways were independently associated with CKD progression. Conclusions: We found higher odds of CKD progression associated with higher 20-HETE, LOX and CYP450 metabolic pathways. These alterations precede CKD progression and may serve as targets for interventions aimed at halting progression.